Democratic Republic of Timor-Leste : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2007)
This Selected Issues paper presents evidence on linkages between investment and growth observed in other countries to gauge the expected impact of increasing public investment in Timor-Leste. The results indicate that the level of capital expenditure envisioned in the government's strategy could significantly boost economic growth and reduce poverty. The paper reviews the major issues related to tax policy reform in Timor-Leste. It also discusses the current direction of Timor-Leste Petroleum Fund asset management and issues that might arise with eventual asset diversification.